Strategi Pemanfaatan Bonus Demografi sebagai Upaya Meningkatkan Pendapatan RSU Pratama Warmare - Beatrik Yunike Yulanda Sroyer; Dasrun Hidayat; Yani Restiani Widjaja (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
This study outlines the strategies for demographic bonus management to increase revenue at RSU Pratama Warmare of Manokwari Regency. The demographic bonus, which is marked by a predominance of the productive-age population, becomes a strategic opportunity when it is managed through adaptive healthcare services. However, high morbidity and unemployment rates among the productive-age group in Manokwari create significant challenges to hospital revenue. This study used a qualitative approach with informants from hospital management, medical staff, and patients. The results indicated that the hospital has carried out several strategies: healthcare services according to age groups, digitalization, strengthened external partnerships, and health education programs. Although patient visits and service efficiency have increased, problems still exist—limited human resources and infrastructure as well as low public health awareness among the population. The study recommends that strategic management of the demographic bonus can improve hospital revenue through cross-sectoral policy support and strengthened internal capacity.